Comparative Study between the Discrete-Frequency Kalman Filtering and the Discrete-Time Kalman Filtering with Application in Noise Reduction in Speech Signals - Leandro Aureliano da Silva; Gilberto Arantes Carrijo; Eduardo Silva Vasconcelos; Roberto Duarte Campos; Cleiton Silvano Goulart; Rodrigo Pinto Lemos (Journal of Electrical and Computer Engineering)
This article aims to carry out a comparative study between discrete-time and discrete-frequency Kalman filters. In order to assess the performance of both methods for speech reconstruction, we measured the output segmental signal-to-noise ratio and the Itakura-Saito distance provided by each algorithm over 25 different voice signals. The results show that although the two algorithms performed very similarly regarding noise reduction, the discrete-time Kalman filter produced smaller spectral distortion on the estimated signals when compared with the discrete-frequency Kalman filter.